The Influence of Financial Literacy, Financial Inclusion, and the Ability to Prepare Financial Reports Against MSME Financial Performance Asahan District - Windi Triana; Inda Arfa Syera (PT Inovasi Pratama Internasional, 2023)
The aim of this research is to examine the influence of financial literacy, financial inclusion, and the ability to prepare financial reports on the financial performance of MSMEs in Asahan Regency. The type of research used is a quantitative method by processing primary data obtained from respondents' answers to questionnaire statements which are distributed directly to respondents and then analyzed using the Statistical Program for Social Science (SPSS) software. The object of this research is MSME actors who are registered with the Office of Cooperatives, Industry, Trade and Investment of Asahan Regency. The analysis techniques used are descriptive statistics, classical assumption tests (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression, and hypothesis testing (F statistical test, and t statistical test, as well as the coefficient of determination test (R2). Based on the research results using a simultaneous test (f test) it can be seen that financial literacy, financial inclusion and the ability to prepare financial reports have a simultaneous effect on the financial performance of Asahan Regency MSMEs. Based on a partial test (t test) it can be seen that the financial literacy variable has a positive and significant effect on financial performance Asahan Regency MSMEs, the financial inclusion variable has a negative and insignificant effect on the financial performance of Asahan Regency MSMEs, and the ability variable to prepare financial reports has no effect on the financial performance of Asahan Regency MSMEs.